2008
DOI: 10.4196/kjpp.2008.12.4.211
|View full text |Cite
|
Sign up to set email alerts
|

The Inhibition of TREK2 Channel by an Oxidizing Agent, 5,5'-dithio-bis (2-nitrobenzoic acid), via Interaction with the C-terminus Distal to the 353rd Amino Acid

Abstract: + channels) were expressed in COS-7 cells, and the channel activities were recorded from inside-out membrane patches using holding potential of 40 mV in symmetrical 150 mM K + solution. Intracellular application of an oxidizing agent, 5,5'-dithio-bis (2-nitrobenzoic acid) (DTNB), markedly decreased the activity of the TREK2, and the activity was partially reversed by the reducing agent, dithiothreitol (DTT). In order to examine the possibility that the target sites for the oxidizing agents might be located in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…4 . To our knowledge, the modulation of Task 3 channels by internal redox reagents has not been studied in detail, however the closely related TREK2 channels are inhibited by the intracellular application of oxidizing agents [48] . It remains also the possibility that in addition to the pore-forming subunits, accessory subunits modulating ion channel function are susceptible to redox regulation during hypoxia.…”
Section: Intracellular Redox Regulation Of Ionic Currents In Glomus Cmentioning
confidence: 99%
“…4 . To our knowledge, the modulation of Task 3 channels by internal redox reagents has not been studied in detail, however the closely related TREK2 channels are inhibited by the intracellular application of oxidizing agents [48] . It remains also the possibility that in addition to the pore-forming subunits, accessory subunits modulating ion channel function are susceptible to redox regulation during hypoxia.…”
Section: Intracellular Redox Regulation Of Ionic Currents In Glomus Cmentioning
confidence: 99%
“…For instance, previous studies have shown that ROS can inhibit TASK-3 channels in peripheral chemoreceptor cells, likely through the oxidation of cysteine residues in the TASK-3 protein [ 16 ]. Additionally, other channels like TREK2 and TASK-2 have also been reported to be modulated by intracellular oxidizing agents [ 17 ], leading to changes in cell excitability [ 10 , 33 ]. Considering this background, we can propose a plausible hypothesis that increased ROS production within the RTN might alter TASK-2 channel biophysical properties, potentially leading to higher H + -mediated inhibition resulting in enhanced chemoreceptor neuron activity.…”
Section: Discussionmentioning
confidence: 99%